Re‐irradiation volumetric modulated arc therapy optimization based on cumulative biologically effective dose objectives. (29th October 2018) - McVicar, Nevin; Thomas, Steven; Liu, Mitchell; Carolan, Hannah; Bergman, Alanah
Abstract: The objective of this note is to introduce a clinical tool that generates ideal base plan dose distributions to enable re‐irradiation volumetric modulated arc therapy (VMAT) optimization based on cumulative biological effective dose objectives for specific organs at risk (OARs). The tool is demonstrated with a lung cancer case that required re‐irradiation at our clinic. First, previous treatment dose is deformed onto the retreatment computed tomography (CT) using commercial software. Then, the in‐house Matlab tool alters the deformed previous dose using radiobiological concepts on a voxel‐by‐voxel manner to generate an ideal base plan dose distribution. Ideal base plans that were generated using the in‐house Matlab tool were compatible with the Varian Eclipse™ treatment planning system. The tool enabled optimization of VMAT re‐irradiation plans using cumulative dose limits for OARs and all OAR cumulative dose objectives were met on the first optimization for the recurrent lung cancer case tested.